Electrospun nanofibers as solid phase extraction sorbents and support for alkylphenols colorimetric probes - Tancu, Yolanda (Rhodes University, Faculty of Science, Department of Chemistry, 2014)
The thesis reports on fabricating alternative solid phase extraction (SPE) sorbents and colorimetric probes based on electrospun nanofibers for alkylphenols (APs). Hydroxyl methylated styrene [poly(co-styrene-CHâ‚ƒOH)] and 3-oxobutanoate styrene [poly(co-styrene-OCOCHâ‚ƒCOCHâ‚ƒ)] copolymers were synthesized and fabricated into sorbent materials by electro-spinning/spraying. The fabricated morphologies consisting of bead free fibers, beaded fibers and particles were evaluated as SPE sorbents using batch experiments. Electropun fibers proved to be better sorbents as they exhibited extraction efficiency that exceeded 95% compared to 60% for beaded fibers and 40% for particles. In view to reduce sample and solvent volumes, smooth fibers were packed into pipette tips as SPE devices that yielded quantitative recoveries of APs from spiked wastewater samples. Recoveries ranged from 70% to 125% with LOD of 0.008, 0.01 and 0.1 Î¼g mLâ »Â¹ for 4-tert octylphenol (4-t-OP), 4-octylphenol (4-OP) and 4-nonylphenol (4-NP) respectively, when using high performance liquid chromatography-fluorescence detector (HPLC-FLD). Furthermore, amino functionalised polydiacetylene polymers (PDAs), citrate capped gold (AuNPs) and silver nanoparticles (AgNPs) were evaluated as colorimetric probes for visual detection of APs. In colloidal studies, AuNPs probe showed a colour change from wine red to green upon introduction of analyte. UV-vis spectroscopy revealed the shifting of the surface plasmon resonance (SPR) peak from 525 nm to 729 nm induced by aggregation of AuNPs. For AgNPs probe, a colour change was observed from yellowish green to brown. Transmission electron microscopy (TEM) studies showed growth of AgNPs. A presumed oxidation of the analyte, forming an absorbing compound at 279 nm in both AgNPs and PDAs probes was also observed. For PDAs probe the colour change was from purple to pink. Concentrations as low as 30 Î¼g mLâ »Â¹ were detectable in all colloidal based probes. Further colorimetric investigations were conducted with electrospun AuNPs-nylon 6 fiber mat. A colour change from purplish red to navy blue at concentrations of 1000 Î¼g mLâ »Â¹ was observed. Electrospun AgNPs "“nylon 6 fiber mat did not show a distinct colour change. High resolution scanning electron microscopy (HRSEM) revealed the analyte inducing the assembly of AuNPs and AgNPs as they covered the surface of the nanofiber mat. Electrospun nanofibers are a platform for analysis and thus tuning their chemistry will lead to sensitive and selective methods
Keywords: Nanofibers; Electrospinning; Extraction (Chemistry); Sorbents; Phenols; Colorimetry; Transmission electron microscopy; High resolution spectroscopy